Hospital dietaries - Hutchinson, Kate M. (My University, 1907)
Introduction: The prolongation of life is the one thing for which we all strive. We labor that we may have means for the enjoyment of this life, but unknowingly we neglect this one thing upon which all happiness depends - the health of the body. "Pain is said to be a blessing in-as-much as it is Nature's warning that something is wrong and needs rectification." This supposition is doubtless true to a certain extent, but it is not always easy to determine just what is wrong or how it is to be corrected. We know, however, that disease is accompanied by an increased waste of tissue, and that health necessitates the rebuilding of new tissue. Now, the only way to accomplish this result is by the administration of proper food; and the object of our study of Hospital Dietaries is to determine the kind of food suitable for the most prevalent diseases and the way in which it is to be prepared.
Citation: Hutchinson, Kate M. Hospital dietaries. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Health; Cause of Disease; Types of Diseases; Treating Disease; Theses